RELIGIOUS RADICALISM, GLOBAL TERRORISM AND ISLAMIC CHALLENGES IN CONTEMPORARY INDONESIA - Choirul Mahfud; Niken Prasetyawati; Wahyuddin Wahyuddin; Zainul Muhibbin; Dyah Satya Yoga Agustin; Heni Sukmawati (Institut Teknologi Sepuluh Nopember, 2018)
Discussing the radicalism of religion and global terrorism is a global challenge that is now a worldwide concern, including for the Islamic community in Indonesia. Research in this paper with an analytical descriptive approach using the documentative method. The general purpose of this research is to understand the root causes of terrorism and religious radicalism in Indonesia? What is the solution of Islam to overcome the problem of religious radicalism and global terrorism? The results show: first, the historical roots of global terrorism and religious radicalism is a very complex portrait of social, political, and economic history. Also, the complexity of local, regional and global problems are interconnected with one another. Second, the Islamic solution to overcome this problem with the Islamic approach of peace for all (rahmatan lil alamin) which prioritizes the path of dialogue and world peace.